2007
DOI: 10.1111/j.1365-3180.2007.00592.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three methodologies for efficient seed extraction in studies of soil weed seedbanks

Abstract: Summary Determination of weed seeds in the soil is tedious and time consuming. To evaluate the different seed extraction methods to improve seedbank estimations, three extraction methods (sieving, cloth bag and flotation) were compared, based on their accuracy and time needed for separation processes and enumeration. Seeds of Datura stramonium,Amaranthus retroflexus,Portulaca oleracea and Plantago major were used to artificially infest soil samples of four textures, namely clay, clay loam, loam and sandy loam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 14 publications
0
37
0
2
Order By: Relevance
“…Contar todas las semillas de un volumen de suelo es la forma más precisa de considerar la mayor cantidad semillas y de especies de un lugar (Mesgaran et al, 2007). Sin embargo, al incluir elementos que nunca germinarán, se sobreestima el BS, cuyo valor reside en los propágulos vivos y viables, que al germinar contribuirán a mantener las poblaciones de plantas adultas.…”
Section: Discussionunclassified
“…Contar todas las semillas de un volumen de suelo es la forma más precisa de considerar la mayor cantidad semillas y de especies de un lugar (Mesgaran et al, 2007). Sin embargo, al incluir elementos que nunca germinarán, se sobreestima el BS, cuyo valor reside en los propágulos vivos y viables, que al germinar contribuirán a mantener las poblaciones de plantas adultas.…”
Section: Discussionunclassified
“…After collecting the dishes, the seeds were separated from the soil by the cloth bag method (Mesgaran et al . ). According to this method, 10 cm × 15 cm fine‐net cloth bags (mesh opening of 0.25 mm) were used.…”
Section: Methodsmentioning
confidence: 97%
“…However, the germination method also has its specific limitations, one being the long-time seedlings may need to germinate and emerge. For example, Mesgaran et al (2007) suggested continuing the process for 2 years. According to their results, in flotation method, a high capacity centrifugation is necessary and limited number and volume of centrifugal vials, as well as the needs for chemical solutions, are among other constraints.…”
Section: Methods Of Separation Of Seeds From Soil Samplesmentioning
confidence: 99%